Roles of gender, race and years of operations in developing outbound strategic Islamic tour packages of Malaysia - Haque, A. K. M. Ahasanul; Ahmed, Faruk; Abdul Razak, Dzuljastri; Hashim, Nurhazirah (Global Academy of Training & Research (GATR) Enterprise, 2017)
The aim of this paper is to provide a profound explanation of some nominal variables as well as evidentially a theoretical explanation from the context of Malaysia. As a quantitative research approach to explain nominal attributes, 107 of travel and tour agents, and tour operators were observed around Malaysia based on a simple random sample designed from a sampling frame of a list of tourism enterprises considered for a population. Innovativeness, communicativeness, collaboration and cooperation, strategy attitude, strategy intention, and strategy behavior are fixed as dependent variables that have been explained based on mainly gender, race and years of operations—from which significant differences between endogenous attributes and some sections of nominal ones were captured— and a meaningful interpretation has been proliferated as a help to provide few effective research, managerial and social implications. A research from Malaysia context partially shortens a broad contextfree meaning. Nevertheless, this result would have a values useful for raising a broader sense of these categorical attributes for those administrations in a context like this, and for the readers around and across Malaysia. The effort was employed, for the first time, in this type of context. So perhaps, this can have a vast theoretical understanding of the Islamic tourism conceptualization from the light of nominally inferential research methods.